The Incidence of Heparin Induced Thrombocytopenia of Chronic Kidney Disease (CKD) Patients on Maintenance of Hemodialysis Visiting to HAH Hospital, Jamia Hamdard, New Delhi - Arif, Mohd Arman; Habib, Mohammad Anwar; Amitabh, Vindu; Najmi, Abul Kalam; Akhtar, Mohd (Indian Journal of Pharmacy Practice)
Aim: The present study was planned to record the incidences of heparin induced thrombocytopenia of Chronic Kidney Disease (CKD) patients on maintenance of hemodialysis. Materials and Methods: This is a prospective observational study, which enrolled 50 patients visiting dialysis unit after satisfying selection criteria. Different parameters like demographic details, educational status, working status, blood pressure, platelets counts, stage of CKD, etc. were recorded. The sources of data included physicians prescribing data, the patient’s medication profile, questionnaire and laboratory test reports. The observations were recorded in the prescribed performs. Results: A total of 50 patients with CKD, 34(68%) were males, 16 (32%) were females, mean age 47.22 years with maximum number belong to age group 48-57 years. A total of 12% patients had a family history of CKD. About 26% of the total patients had a single concomitant whereas 24% of the patients had double concomitant conditions and the most frequent concomitant condition was anemia followed by hypertension. The Hb level was lower than the nomal limits and their eGFR level below 15ml/min/1.73m2 hence they were all at stage 5 of CKD. All patients showed different platelet level and upon dialysis, it was decreased markedly. This showed that heparin induced thrombocytopenia during dialysis. Only 2 (4%) of the patient had clot formation in dialyzers and extracorporeal circuit and decrease in platelet count during hemodialysis. Conclusion: This study strongly recommends the monitoring of platelet count in CKD on maintenance of hemodialysis receiving heparin.
Keywords: Heparin; Thrombocytopenia; Chronic Kidney Disease (CKD); Hemodialysis; Heparin induced thrombocytopenia.